KARAKTERISASI BIO-OIL TANDAN KOSONG KELAPA SAWIT DENGAN PENAMBAHAN KATALIS Ni/NZA MENGGUNAKAN METODEFREE FALL PYROLYSIS - Santiyo Wibowo; Lisna Efiyanti; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2017)
Biomass resource mainly from forest industries waste such as oil palm empty fruit bunches (TKKS) is abundantly available, Currently, the utilization of TKKS as pyrolysis products is still limited to charcoal product, activated charcoal and charcoal briquettes. On the other hand, research on bio-oil manufacturing from biomass using fast pyrolysis method may increase hydrocarbons and calorific values, however the amount of catalyst used is higher than the biomass. This paper observes data and information on the characteristics of bio-oil made from oil palm empty fruit bunches through the addition of Ni/NZA as a catalyst. The optimal results (yield 30.27%, pH 2.94, specific gravity 1.068, viscosity 44 cSt and calorific value 29.38 MJ/kg with flame in medium category) were obtained with the addition of 6% catalyst. The bio-oil produced was dominated by acetic acid, phenol and benzene or toluene, and there were also alkene hydrocarbons compound, for instance hexadecene and aromatic hydrocarbons naphthalene.